Blockade of Autophagy Prevents the Development and Progression of Peritoneal Fibrosis - Shi, Yingfeng; Hu, Yan; Wang, Yi; Ma, Xiaoyan; Tang, Lunxian; Tao, Min; Qiu, Andong; Zhuang, Shougang; Liu, Na (Frontiers in Pharmacology, 2021)
Peritoneal fibrosis (PF) is a major cause of ultrafiltration failure in long-term peritoneal dialysis (PD) patients. Nevertheless, limited measures have been shown to be effective for the prevention and treatment of PF. Some views reveal that activation of autophagy ameliorates PF but others demonstrate that autophagy promotes PF. It is obvious that the role of autophagy in PF is controversial and further studies are needed. Here, we investigated the role of autophagy in rat models of PF and damaged cultured human peritoneal mesothelial cells (HPMCs). Autophagy was highly activated in fibrotic peritoneum from two PF rat models induced by 4.25% peritoneal dialysate fluid (PDF) and 0.1% chlorhexidine gluconate (CG). Blockade of autophagy with 3-MA effectively prevents PF in both models and reversed epithelial to mesenchymal transition (EMT) by down-regulating TGF-β/Smad3 signaling pathway and downstream nuclear transcription factors Slug and Snail. Treatment with 3-MA also inhibited activation of EGFR/ERK1/2 signaling pathway during PF. Moreover, 3-MA prominently decreased STAT3/NF-κB-mediated inflammatory response and macrophage infiltration, and prevented peritoneal angiogenesis through downregulation of β-catenin signal. In addition, TGF-β1 stimulation up-regulated autophagic activity as evidenced by the increased autophagosome in vitro. Exposure of HPMCs to TGF-β1 resulted in the induction of EMT and activation of TGF-β/Smad3, EGFR/ERK1/2 signaling pathways. Treatment with 3-MA blocked all these responses. In addition, delayed administration of 3-MA is effective in reducing EMT induced by TGF-β1. Taken together, our study indicated that autophagy might promote PF and 3-MA had anti-fibrosis effect in vivo and in vitro. These results suggest that autophagy could be a potential target on PF therapy for clinical patients with long-term PD.